The knowledge management and competitive advantages of small and medium-sized enterprises - Nurdasila Darsono, Nurlina, Jasman J. Ma’ruf, Nasir, (Opción, 2019)
The purpose of this study is to examine the effect of Knowledge Management on Business Performance through Competitive Advantages. Data analysis techniques are done by using SPSS. The results showed that knowledge management has a positive and significant influence on business performance and competitive advantage, and competitive advantage mediates partially (mediation) the influence between knowledge management and business Performance. In conclusion, Organizations that have superior knowledge will be able to combine all of their internal resources in a new way so they can provide more value to their customers.